SISTEM INFORMASI GEOGRAFIS PEMETAAN BENCANA ALAM KOTA BREBES MENGGUNAKAN METODE EXTREME PROGRAMMING - Warjiyono, Warjiyono; Aji, Sopian; Permesti, Tri Indah (Jurnal Pilar Nusa Mandiri, 2019)
Public service is an activity of service for every citizen and resident for goods, services, and / or administrative services provided by public service providers, namely the Regional Disaster Management Agency (BPBD) of Brebes Regency. The quality of public services must have the principle of openness or transparency, easily accessible, accountability and cling to the principles of efficiency and effectiveness. But in fact the current information and reporting of disasters is still conventional. This study aims to reflect and build a Web-Based Disaster Geographic Information System using Extreme Programming method. The research method uses qualitative methods with descriptive data analysis techniques. Data obtained by observation and interviews. The benefit of this application is to improve services to the Brebes Regional Disaster Management Agency also useful for internal from the Implementing Party or Admin who can manage Disaster Area data online, accurately, and quickly. As well as greatly helping the community to obtain maps of information on disaster-prone areas, the latest disaster information and the community can report directly on disaster events so that the Regional Government can directly handle the disaster.